University Students' Reflection on Learning English through Drama - Jihan; Hendriwanto (Borneo Educational Journal (Borju), 2021)
Speaking skills is common in higher education and can be a significant source of anxiety and stress. This study was designed to measure the student's experience and self-esteem of speaking skills through drama performance. The research was conducted a qualitative interviewing method and analyzed using narrative inquiry. This study participants were English department students who have completed the drama subject in the fifth semester. The instrument used for collecting the data was an interview guide. This study revealed that drama makes students feel confident and self-esteem, freedom of expression, and improved speaking skills. It is supported by students' preparation in action and lecturers' feedback and appreciation in drama. The implications for lecturers involved in speaking performance include drama to consider their involvement in the process of student engagement in preparing for the performance. Because with the preparation time, the input and praise they receive can significantly affect their self-confidence, self-esteem, and the results of their appearance.